Energy consumption performance using natural ventilation in dwelling design and CFD simulation in a hot dry climate: A case study in Sudan - Jeradat, Amer; Elhassan, Zeinab A. (Frontiers in Built Environment, 2023)
Abstract Sudan is taking a proactive approach to environmental sustainability and is making ‎progress in several key areas. These initiatives are a positive step towards a more ‎sustainable future for the country. This article assesses an architectural design utilizing an ‎Energy Consumption consideration of Natural Ventilation in a hot-dry climate (State of ‎Khartoum, Sudan, Africa) at residences designed for this climate. This is to address the ‎natural ventilation contribution of heat transfer and temperature conditioning in urban areas ‎and improve the use of passive construction for the building under the challenges of power ‎costs and availability. The research methodology considered a combination of building ‎modeling with CFD integrated with IEVS Autodesk software to model natural ventilation ‎and simulate energy consumption by incorporating natural ventilation into the home design. ‎The results showed that it was possible to maintain a comfortable indoor temperature in ‎summer. The best-case scenario for natural ventilation in terms of energy savings occurred ‎when the design point of internal air speed is around 0.7 m/s then 95% of the indoor areas ‎will have an average air speed between 0.43 and 0.9 m/s. The yearly energy savings as the ‎primary objective was 71.1%. The worst-case scenario occurred in the east/west direction, ‎‎80% of the interior has an airflow between 0.05m/s and 0.01m/s, near the window opening ‎where the airflow is around 0.1m /s. This study was the first research in Khartoum to design ‎clean and energy-saving sustainable architecture. The architectural design process in the ‎urban region of Alazhari City for energy-efficient living was implemented and defined in a ‎city quarter in Khartoum.‎